Engines of change party factions in American politics, 1868-2010 - DiSalvo, Daniel (Oxford : Oxford University Press, 2012)
This title provides an account of the role of national intra-party 'factions' in American politics. Drawing from the last 150 years of American political history, DiSalvo explains how factions have shaped the parties' ideologies, impacted presidential nominations, structured patterns of presidential governance, and much more.
Description based on online resource; title from PDF title page (viewed on Apr. 20, 2012).
Includes bibliographical references and index.
Keywords: Political parties -- United States -- History